Parking Analysis on Bogor Agricultural University Campus - Syaiful, Syaiful; Zein, Anggi Muskita; Rulhendri, Rulhendri; Aminda, Renea Shinta (Universitas Ibn Khaldun Bogor, 2023)
Andi Hakim Nasution Building is a facility located at Bogor Agricultural University. Andi Hakim Nasution Building is located in the main campus area of Bogor Agricultural University, Jl, Meranti, Babakan Village, Dramaga District, Bogor Regency. This building is used for the offices of lecturers, staff and leaders, so that one of the motorized vehicle parking facilities is one of the needs of this building, but the existing parking facilities are still not neatly arranged. then it is necessary to study the analysis of parking on the Bogor Agricultural University campus. So that it can provide alternative parking control at the Andi Hakim Nasution Building so that no more motorized vehicles are found that are not neatly parked. This study aims to obtain the existing capacity of parking locations in the Andi Hakim Nasution Building and obtain parking characteristics (accumulation, duration of each vehicle, parking space turnover rate and parking index) of motorized vehicles in the Andi Hakim Nasution Building area. This study uses quantitative methods, this data collection is carried out by observation as primary data, among others, data on the number of vehicles entering, data on the number of vehicles out, data representing peak hours, peak days, normal hours, normal days, the number of Parking Space Units (SRP). The secondary data obtained by researchers through sources that have become data, which have conformity with the data that researchers are looking for in the study area, namely the area of parking area space. The result of this study is that the existing parking lot obtained secondary data with a survey method so as to produce existing data covering an area of 630m2 motorcycle parking area with a capacity of 180 ( Parking Space Unit) SRP and a tilt angle of 90 ° at the Andi Hakim Nasution Building. In this analysis study, the largest accumulated stasis capacity was 251 vehicles with an average parking duration of 9:57 hours on Tuesday, May 30, 2023. During the ten days of the survey conducted, it was found that the maximum parking volume was 403 vehicles with a maximum vehicle parking accumulation of 351 vehicles which occurred on Monday 5 June 2023, the highest motorcycle parking turn over at the Andi Hakim Nasution Building reached 223.89%, indicating that the performance of motorcycle parking was quite high. The capacity of motorcycle parking spaces at the Andi Hakim Nasution Building cannot meet existing parking needs.